ANALYSIS OF STUDENT'S LEARNING INDEPENDENCE IN DISTANCE LEARNING DURING THE PANDEMIC USING RASCH MODEL: LEARNING INDEPENDENCE - Eva, Eva Dwi Kumala Sari (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2024)
Due to COVID-19 pandemic, the government needs to initiate new policies that support the transition from face-to-face to online learning. This study aimed to examine the impact of student independence on distance learning. The sample included 835 elementary, middle, and high school students in Bekasi City and Regency, selected using proportional cluster random sampling. The data were collected using a student learning independence questionnaire. Furthermore, the study used non-experimental quantitative design and analyzed data through the Rasch model. The WINSTEPS software helped determine the instrument validity and reliability. Moreover, students’ discipline in online learning was determined using descriptive statistics of mean and standard deviation and logit item value and individual scores. The scores were specifically used to assess their readiness based on gender, age, ethnicity, and field of study. The results showed that student independence was moderate at 69% based on government regulations on online learning patterns. This condition influences the' mentality of students and learning independence in a conducive environment.